Javanese antique furniture and folk art : the David B. Smith and James Tirtoprodjo collections - 493383 Carpenter, Bruce W.; Backus, Charles 493389; Adnyana, Ida Bagus Putra, 1958- 493390 (Singapore, SI : Editions Didier Millet, 2009)
Includes bibliographical references (p. 309) and index